23 Years of Reformation, Freedom is Still a Utopia - Ananda, Muhammad Alfian Rizki; Muttaqin, Labib (Interdisciplinary Social Studies, 2022)
Background: Freedom of expression is still a problem in the implementation of democracy in Indonesia. Amnesty noted that throughout 2020 there were 132 cases of alleged violations of the right to freedom of expression using the ITE Law with a total of 156 victims, among them 18 activists and four journalists. In 2021, there have been 56 similar cases with a total of 62 victims. Aim: This research aims to discuss Indonesia’s reformation along with its obstacle throughout the years. Method: This study used a qualitative approach and a case study. The data was gathered from a number of different places. The sources explore the challenges that Indonesia has faced in its reformation over the years. Findings: The ITE Act is still needed to prevent and punish crime in the digital world. However, there are several articles in this Law that need to be revised because there are multi-interpretation articles, rubber articles, and semantic improvements of several articles to be better. If it is not immediately revised, then the public will be afraid to convey criticism for fear of making the critic's party entangled in the punishment of libel and defamation charges.